DEFINITION OF THE EFFICIENCY OF NITRATE REMOVAL FROM WATER USING THE REVERSE OSMOSIS METHOD - GOMELYA, MUKOLA; TRUS, INNA; VAKULENKO, ANNA; FATIEIEV, DANYLO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Nitrates are usually present in all natural water bodies. Their source is usually agricultural production, municipal and domestic wastewater, and surface runoff. Elevated concentrations of nitrates in drinking water pose a serious threat to both the environment and human health, and their removal and content control are quite relevant. The content of nitrates in drinking water is regulated by the requirements of regulatory documents and, according to the recommendations of the World Health Organization, should not exceed 50 mg/dm3. Since nitrates are stable and highly soluble water anions with low precipitation or adsorption capabilities, they are quite difficult to remove from water. Currently, processes such as electrodialysis, reverse osmosis, ion exchange, catalytic and biological degradation are used to purify water from nitrates. The choice of a specific method for removing nitrates from water is determined by the technical means of purification, the ultimate purpose of the purified water, the cost, and the degree of purification. Baromembrane methods, in particular reverse osmosis methods, are promising, but their possibilities for nitrate removal have not been sufficiently studied. The reverse osmosis process for the removal of nitrates from water has been studied. A module with a low-pressure Filmtec TW30-1812-50 membrane was used for reverse osmosis water purification from nitrates. The efficiency of nitrate removal on a reverse osmosis membrane was low, and the selectivity of the membrane increased with increasing permeate recovery from 10 to 90% at an initial nitrate concentration of 3.0 mg/dm3, from 34.32 to 72.90%, at 10.0 mg/dm3, from 37.14 to 69.20%; at 30.0 mg/dm3, within 74.86-81.92%, and at 150.0 mg/dm3, within 82.92-83.11%. In general, selectivity increased with increasing nitrate concentration in the water. The residual nitrate concentrations in the water were significant in almost all cases and often exceeded the permissible level in drinking water. At the same time, the nitrate content in the concentrates was low, which complicates the problem of their disposal.
Keywords: reverse osmosis; nitrates; water purification; selectivity; concentration